Yield curve momentum - Markus Sihvonen (Bank of Finland, 2021)
I analyze time series momentum along the Treasury term structure. Past bond returns predict future returns both due to autocorrelation in bond risk premia and because unexpected bond return shocks increase the premium. Yield curve momentum is primarily due to autocorrelation in yield changes rather than autocorrelation in bond carry and can largely be captured using a single bond return or yield change factor. Because yield changes are partly induced by changes in the federal funds rate, yield curve momentum is related to post-FOMC announcement drift. The momentum factor is unspanned by the information in the term structure today and is hence inconsistent with standard term structure, macrofinance and behavioral models. I argue that the results are consistent with a model with unpriced longer term dependencies.
urn:nbn:fi:bof-202111162106
Keywords: G12; E43; E47; 330; Bond risk premia; time series momentum; term structure models; post-FOMC announcement drift